Zn1−xSixO: Reduced photosensitivity, improved stability and enhanced conductivity. (June 2018) - Srivastava, Tulika; Bajpai, Gaurav; Liu, Shun Wei; Biring, Sajal; Sen, Somaditya
Abstract: Effect of different wavelengths (350, 380, 390, 400, 450, 550 & 650 nm) of light on surface conductivity of sol-gel synthesized Zn1−x Six O material has been observed. Enhancement in conductivity at all wavelengths of light had been attributed to enhanced charge carrier concentration with silicon doping. Reduction in sensitivity for UV and visible light wavelength indicates reduction of surface defects and deep level traps with Si 4+ incorporation. Enhanced photo stability with Si 4+ doping makes it an appropriate material for transparent electrodes used in various display and electronic devices. Graphical abstract: Unlabelled Image